SPINDLE: A New Hope for Tremor Patients - Bilawal, Makhdoom; Arjun, Urwa; Bai, Vineeta; Shamim, Laiba; Umar, Muhammad (Nepal Journal of Neuroscience, 2025)
Tremors are involuntary, rhythmic movements of one limb or a part of the human body produced by irregularly synchronous contractions of reciprocally innervated muscles. Tremors affect significantly on individual’s capability to perform tasks of daily routine and reduce their independence and quality of life. It may also affect mood, sleep, ways of thinking, and fundamental motor functions.The research team of Gwangju Institute of Science and Technology (GIST), Korea took the responsibility and crowned themselves as the pioneer in the world of modern medical sciences by inventing the SPINDLE therapy technique. Their research was published in IEEE Transactions on Neural Systems and Rehabilitation in which the Spherical Parallel Instrument for Daily Living Emulation (SPINDLE) was introduced. SPINDLE is a robotic rehabilitation device that provides resistive forces in 3-dimensional rotations. It is incorporated with a 6-axis force or torque sensor and a Virtual Reality (VR) System to enable an interactive ADL rehabilitation experience. SPINDLE sessions may also contribute valuable insights into neuroplasticity and motor learning, which could refine treatments for various neurological disorders. The promising outcomes endorse that SPINDLE can emerge as a preferred device in tremor rehabilitation programs. It is quite important to introduce new and interesting features in SPINDLE-based therapy that could be more effective and enjoyable for patients of tremors whose life is already frustrated by tremors.